2006
DOI: 10.2174/156802606777864935
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Signaling of Monocytic Differentiation in Human Leukemia Cells: Role of MAPK Pathways in Transcription Factor Activation

Abstract: Among the many important physiological functions of the activated vitamin D receptor (VDR) is the signaling of monocytic differentiation, first demonstrated by conversion of malignant myeloid leukemia cells to nonproliferating cells with mature monocyte/macrophage appearance. However, the understanding of how 1, 25-dihydroxyvitamin D3 (1,25D) signals monocytic differentiation is still developing. Recent advances summarized here include the role of the principal "mitogen-activated protein kinase" (MAPK) pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…ERK1/2, isoforms of p38MAPK as well as JNK, are all activated by 1,25D, and their regulation of CD14 expression converges on C/EBPβ (2325). Mef2C, which lies downstream of ERK5 and is required, at least partially, for CD14 expression, can perhaps also regulate CD14 expression by activating C/EBPβ.…”
Section: Resultsmentioning
confidence: 99%
“…ERK1/2, isoforms of p38MAPK as well as JNK, are all activated by 1,25D, and their regulation of CD14 expression converges on C/EBPβ (2325). Mef2C, which lies downstream of ERK5 and is required, at least partially, for CD14 expression, can perhaps also regulate CD14 expression by activating C/EBPβ.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in human models of AML have indicated that the MAPK pathways regulate 1,25D-induced monocytic differentiation [13, 14, 18, 25, 26]. Prior work in our laboratory has demonstrated a regulatory function in 1,25D-induced differentiation of JNK activity and the consequent phosphorylation of the c-Jun protein, a component of AP-1 transcription factor dimer, [13, 27].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we demonstrated that KV-1 enhanced 1,25-(OH) 2 D 3 -and ATRA-induced differentiation in HL-60 leukemia cells, which are widely used as a model system for Previous studies have revealed that PKC activation is necessary for the differentiation of HL-60 cells (16,22) and mitogen-activated protein kinases (MAPKs) are downstream elements in the PKC signaling pathway of HL-60 cells (23). The c-Jun N-terminal kinase (JNK) signaling module is also known to participate in myeloid cell differentiation (24,25).…”
Section: Discussionmentioning
confidence: 70%